Historical deconstruction in Return to Ithaca (2016), by Leonardo Padura and Laurent Cantet - Mengzhen, Jia (2020)
In the last century, the most prominent event in Cuban history was the 1959 Revolution, an influential social movement, especially among the generation that participated in the Revolution and began to experience the postrevolution. In the fifties of the last century, Cubans suffered a spiritual and physical trauma difficult to overcome. The characters of Return to Ithaca (2016) represent that period, reflect of a microworld of the general situation of the time. The return of one of them from Spain causes the meeting between the five friends on a rooftop in La Habana. The discussion between them only manages to revive hope at the same time as the disappointment of their past, present and future. As the work is presented under the structure of a script, it respects the three rules of the theater, which favors a view from the theatrical interpretation. For this work we will rely on the sociological and psychological analysis, in order to better understand Padura and Cantet´s recreation of the general situation of that period. Our analysis aims to show that the intertextuality between literature and history allows us to understand an epoch, and the human experiences that take place in it, in a more vivid way. Padura and Cantet not only present a script of a reunion between five old friends, but also state that they all face a reconsideration of the illusions lost by and in the Revolution, in a painful but, at the same time, humorous, caustic and even joyful way.